Domestic Causes of Currency Crises Policy Lessons for Crisis Avoidance - Reisen, Helmut (OECD Development Centre Working Papers, 1998)
The recent currency crises in Latin America and Asia have hit countries with strong macroeconomic fundamentals but weak domestic financial systems. Private capital flows, attracted by disorderly financial liberalisation and exchange rate pegs, reversed abruptly when financial-sector weaknesses became apparent. Often, domestic financial systems have proved too weak a conduit for heavy capital inflows, resulting in declining credit quality and financial vulnerability to speculative currency attacks. Developing countries are therefore advised to pay close attention to indicators of financial vulnerability, in particular to short-term debt levels as a fraction of official foreign exchange reserves, as well as to currency and maturity mismatches in private-sector balance sheets. This paper points to the avenues that can be pursued to avoid a rise in the vulnerability indicators above critical levels ... Some of these avenues are uncontroversial, but deceptively hard to implement. Good ...